Distribuição espacial da hanseníase na Província de Misiones-Argentina and Southern Brazil - Oliveira, Keurilene Sutil de (2019)
The objective of this study was to analyze the epidemiological situation of leprosy in the province of Missiones-Argentina and Southern Brazil, according to spatial distribution. It is an ecological study, having as units of analysis the departments of Misiones in Argentina and municipalities of the South Region of Brazil. The population were cases of leprosy in the territory of the analysis, covering the years 2010 to 2016. Spatial analyzes were performed and the relative spatial risk and confidence interval were calculated in 95%. A total of 10,319 new cases were recorded, the most endemic state was Paraná, representing 70.2% of the cases recorded. There was a predominance of multibacillary operational classification (79.8%) and Physical Inability Grade (50.6%). Regarding the incidence, a hyperendemic situation was observed in 65.5% of the municipalities / departments studied. Areas of significant relative risk were found in most parts of Paraná, and in the Santa Catarina coast, in the interior of Rio Grande do Sul and in the province of Misiones, Argentina, indicating a high probability of similar disease in adjacent areas. Against all odds of the border scenario, we suggest the development of studies in spatial clusters, including, in addition to the control and surveillance actions established by the Ministries of Health of the countries involved, new strategies for active search, education campaigns and actions aimed at early diagnosis and treatment.